Les Ultras à Montréal entre tension, réappropriation et paradoxes - Bachir Sirois-Moumni (Communiquer)
The objective of this article is to focus on the cultural signification of soccer as produced and expressed by Ultras supporters’ groups in the North American context. Stemming from a subcultural perspective, this analysis is based on a body of literature detailing the Ultras’ culture in Montreal (Local Press Review [1992–2016]), semi-structured interviews and an ethnographic participant observation [2011–2016]). This article describes how the Ultras were able to consolidate their place in Montreal’s soccer cultural landscape through a series of tensions, reappropriations and paradoxes. It is argued that Ultras must be understood as a fragmented cultural manifestation, consisting of multiple dynamics of domination-negotiation-resistance in relation to the local and international contexts in which they take shape.